2021
DOI: 10.1016/j.redox.2021.102112
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the pleiotropic and specific phenotypic consequences of missense mutations in the multifunctional NAD(P)H:quinone oxidoreductase 1 and their pharmacological rescue

Abstract: The multifunctional nature of human flavoproteins is critically linked to their ability to populate multiple conformational states. Ligand binding, post-translational modifications and disease-associated mutations can reshape this functional landscape, although the structure-function relationships of these effects are not well understood. Herein, we characterized the structural and functional consequences of two mutations (the cancer-associated P187S and the phosphomimetic S82D) on different ligation states wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 51 publications
6
62
0
Order By: Relevance
“…Thus, we will focus in this section on the structural and dynamic consequences of ligand binding to NQO1 in an attempt to obtain some insight into their regulatory effects on NQO1 interactions with protein partners (always from an NQO1 point of view). NQO1 apo exists as a stable and expanded dimer characterized by significantly large conformational flexibility [ 65 , 67 , 68 , 69 , 111 , 128 , 129 , 130 , 131 ]. Although no high resolution structural model is available for this state, recent kinetic studies using hydrogen–deuterium exchange mass spectrometry (HDXMS) have identified a minimal stable core that holds the protein dimer, while most of the protein exists forming a highly dynamic structural ensemble, including the FAD and substrate binding sites in non-competent states for binding [ 132 ].…”
Section: Nqo1 As a Protein Chaperone: Current Knowledge And Potential...mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we will focus in this section on the structural and dynamic consequences of ligand binding to NQO1 in an attempt to obtain some insight into their regulatory effects on NQO1 interactions with protein partners (always from an NQO1 point of view). NQO1 apo exists as a stable and expanded dimer characterized by significantly large conformational flexibility [ 65 , 67 , 68 , 69 , 111 , 128 , 129 , 130 , 131 ]. Although no high resolution structural model is available for this state, recent kinetic studies using hydrogen–deuterium exchange mass spectrometry (HDXMS) have identified a minimal stable core that holds the protein dimer, while most of the protein exists forming a highly dynamic structural ensemble, including the FAD and substrate binding sites in non-competent states for binding [ 132 ].…”
Section: Nqo1 As a Protein Chaperone: Current Knowledge And Potential...mentioning
confidence: 99%
“…Although no high resolution structural model is available for this state, recent kinetic studies using hydrogen–deuterium exchange mass spectrometry (HDXMS) have identified a minimal stable core that holds the protein dimer, while most of the protein exists forming a highly dynamic structural ensemble, including the FAD and substrate binding sites in non-competent states for binding [ 132 ]. The local stability of this state is very sensitive to mutations [ 131 ]. This remarkable conformational flexibility makes NQO1 apo likely the most relevant state to understand the intracellular stability of NQO1, since the flexible CTD acts as an initiation site for rapid degradation through ubiquitin-dependent and -independent proteasomal pathways [ 88 , 117 , 131 ].…”
Section: Nqo1 As a Protein Chaperone: Current Knowledge And Potential...mentioning
confidence: 99%
See 3 more Smart Citations